Hip Corticosteroid/Anesthetic Injections—Are the reported rates of osteoarthritis progression and femoral head collapse real?. Issue 7 (30th July 2021) - Abraham, Paul; Varady, Nathan; Small, Kirstin; Shah, Nehal; Beltran, Luis; Meek, Wendy; Eberlin, Christopher; Martin, Scott; Kucharik, Michael
Objectives: In the absence of definitive Level I evidence regarding the safety of hip CSI, there have been an increasing number of retrospective case series studying outcomes after hip corticosteroid injection (CSI). Recent studies have suggested that hip CSI may be associated with increased rates of avascular necrosis (AVN), subchondral insufficiency fracture (SIF), femoral head articular surface collapse, and accelerated progression of osteoarthritis (OA), but these studies do not compare against a control arm matched for baseline OA severity or exclude patients with pre-injection AVN or SIF from analysis, causing selection bias. The purpose of this study was to compare complication rates in patients treated with and without CSI, while minimizing the aforementioned selection bias. Methods: For all patients at our institution who had undergone hip CSI between 2007 and 2019 and hip magnetic resonance imaging (MRI) within the preceding 12 months (CSI cohort), two musculoskeletal radiologists retrospectively reviewed hip radiographs taken within 12 months prior to and after CSI and graded OA severity (modified Kellgren-Lawrence classification) and femoral head collapse, blinded to cohort and timepoint. The same was done for a hip control cohort (matched for age, sex, BMI, and OA severity on baseline radiograph reports) that had undergone hip MRI and pre- and post-MRI hip radiographs within 12 months. A third reader arbitrated discrepant reads. OA progression was defined as an increase in modified Kellgren-Lawrence grade ≥1 between radiographs. Matched pairs with at least one incidence of pre-existing AVN or SIF on index MRI were excluded for analysis. Results: 186 hips in the CSI group [mean ±95% CI age: 55.8±2.1, mean±95% CI BMI: 27.5±0.8, 69 (37.1%) males, 100 (53.8%) right hips] and 186 hips in the control group [mean ±95% CI age: 55.7±2.3, mean±95% CI BMI: 28.0±0.8, 69 (37.1%) males, 96 (51.6%) right hips] were included in this study. There were no significant differences between groups in age, gender, BMI, laterality, baseline OA severity, or baseline AVN/SIF on index MRI. Analysis of adjudicated radiographic outcomes were performed after exclusion of 61 matched pairs with at least 1 instance of pre-existing AVN or SI (Table 1). Rates of OA progression (5.6% vs. 2.4%; p=0.33), new AVN or SIF (1.6% vs. 0.0%; p=0.50), and new femoral head collapse (3.2% vs. 2.4%; p=1.000) were all similar between groups. Of the 4 cases of new femoral head collapse in the CSI group, 2 were classified as femoral head remodeling secondary to OA, leaving only two (1.6%) definitive femoral head collapses secondary to AVN or SIF. Of the 3 cases of new femoral head collapse in the control group, 2 were classified as femoral head remodeling due to an unknown etiology, leaving only one (0.8%) definitive femoral head collapses secondary to AVN or SIF. (Tables 1, 2, 3) Conclusions: When controlling for baseline OA severity and pre-existing AVN or SIF, patients treated by CSI in our study showed OA progression in only 6% of cases and new femoral head collapse in only 3% of cases, which was not significantly greater than control and similar to the expected progression of natural disease. Future multicenter, randomized, double-blind, placebo-controlled trials investigating safety of hip CSI are needed. :